SYMBOLIC POTENTIAL OF RAMBUT MONTE LAKE IN BLITAR EAST JAVA AS A TOURISM INDUSTRY - Dwi Sulistyorini (Prosiding Seminar Nasional dan Internasional HISKI, 2020)
The Rambut Monte lake in Krisik Village, Blitar, is a historical and cultural heritage tourism destination that is continuously preserved and promoted. The symbolic potential behind the story of the Rambut Monte lake is what attracts tourists to visit it. The artifacts in Rambut Monte as a relic of the Majapahit kingdom have become historical tours that need to be explored for their attractiveness. Apart from that, the myth of the Rambut Monte lake is a community belief that is continuously maintained to protect the cosmos. The promotion of Rambut Monte tourism using a cultural mechanism of production, distribution, and consumption can make the Rambut Monte lake known by the wider community.